Testwiseness, Digital Accessibility, and Attitudinal Disposition to Computer-Assisted Testing among Undergraduate Students in North-West, Nigeria - Abdul-Wahab Ibrahim; Yusuf Olayinka Shogbesan; Abdullahi Iliyasu (MO.RI Publishing, 2022)
The purpose this study was to determine whether undergraduate students' testwiseness and access to digital devices are key factors critical to enhancing their attitude towards Computer-Assisted Testing (CAT) in some selected Universities in the North-west geo-political zone of Nigeria. It also examined if a significant difference existed in undergraduate students' attitude to CAT in Universities in the North-west Nigeria. These were with a view to improving the CAT outcome directed towards certifying the quality in education by the Nigerian universities. The study adopted a descriptive survey research design. The sample consisted of an intact class of 5,880 Part I undergraduate students selected from federal and state-owned Universities in the North-west. A self-developed instrument tagged: "Undergraduate's Testwiseness Digital Accessibility and Attitude Inventory (UTDAAI)", was used to collect data.  Data were analysed using Stepwise Multiple Regression and independent t-test statistics. The results revealed that testwiseness and digital accessibility are not significantly combined to influence undergraduate students' attitude to CAT in Universities in the North-west Nigeria. However, there existed a positive significant relationship between testwiseness and digital accessibility. Further, there was no significant sex difference in undergraduate students' attitudinal disposion to CAT in Universities in the North-west Nigeria. The study concluded that testwiseness was not a most potent predictor of students' attitude to CAT irrespective of their access to digital devices in the University. It was recommended that Universities' Management should invest considerable resources in developing rapid response digital intervention initiatives to support the learning, teaching and assessment transition for undergraduate students in the country.